Empowerment of Rural Zulu Women through Popular Adult Education in South Africa: A Case Study of the National Association for Women's Empowerment (NAWE) Program in KwaZulu-Natal - Zilungile Sosibo (Adult Education Research Conference, 1999)
This paper reports the study on grassroots Zulu women in the NAWE program. The purpose was to investigate whether the women were empowered. The research question was: Are the women empowered, if so, in what ways and how do they define empowerment? Methods of data collection included interviews, participant observation, and document analysis.